Peningkatan Pemahaman Remaja tentang Prosedur Administrasi Pernikahan melalui Kegiatan Sosialisasi KPM di Desa Cikadu - Muhammad Nur Ilham; Dulnasir Dulnasir; Adriansyah Adriansyah (IKHTIAR: Jurnal Pengabdian Kepada Masyarakat, 2026)
Abstract: Lack of adolescents’ understanding of marriage administrative procedures often leads to delays in marriage registration, incomplete documents, and unregistered marriages. This condition is commonly found in rural areas, including Cikadu Village, where access to administrative information remains limited. This Community Service Program (KPM) aimed to improve adolescents’ understanding of marriage administration procedures through structured socialization activities. The methods used included educational socialization, interactive discussions, and simulations of the marriage registration process at the Office of Religious Affairs (KUA). The focus of the material covered marriage documents, the marriage registration flow at the KUA, administrative requirements, and technical aspects that are often unknown to adolescents. The results showed an improvement in adolescents’ knowledge and awareness regarding the completeness of documents and the importance of legal marriage registration. This activity is expected to serve as a preventive effort in preparing adolescents for marriages that are legally valid according to both religious and state regulations.